Current Trend of Intravenous Fluid Use In Medicine Wards in a Teaching Hospital - Tajreen, Tania; Zahed, ASM (Journal of Chittagong Medical College Teachers’ Association, 2017)
Background: Some hospitalized patients may not be able to eat and drink and often have depleted fluid levels and electrolyte imbalance. So, intravenous (IV) fluid therapy is a part of everyday clinical practice. Aims: This study was carried out to assess the extent of rational use of IV fluid in indoor patients of medicine wards of Chittagong Medical College Hospital (CMCH). Materials and methods: This cross sectional observational study was done in CMCH from April to November 2014. One hundred and ninety four (n=194) patients getting IV fluid were selected by purposive sampling. All relevant information for each study subject was collected by ‘Observing Method’ using a data collection sheet after getting informed written consent. Variables were checked. Results were matched with standard guidelines. Results: Male patients were 1.3 times more than female. Acute abdomen (20.62%) Acute febrile illness (11.85%) Poisoning (11.34%) Stroke (10.31%) and Acute watery diarrhea (9.28%) were common indications for giving IV fluid. Status of hydration was properly assessed in 82.99% patients. Commonly used fluids were 5% DNS (34.02%) NS (17.01%) CS (7.22%). Amount of fluid was appropriate in 90.20% patients but constituents were appropriate only in 52.06% patients. Most of the patients (76%) had received IV fluid for one day. Thirteen (6.70%) patients had suffered from IV fluid related complications. Conclusion: Considering assessment of status of hydration, amount and constituents of fluid, 64 (33%) patients had received IV fluid in a rational way. This study highlights the importance of multicentre study to formulate a national guideline. JCMCTA 2017 ; 28 (1) : 32 - 37